1999
DOI: 10.1892/0891-6640(1999)013<0587:trbspc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Some Plasma Clearance Methods for Estimation of Glomerular Filtration Rate in Dogs with Pyometra

Abstract: The purpose of the present study was to compare different pharmacokinetic models for estimation of glomerular filtration rate (GFR) in 50 dogs with pyometra. GFR was estimated by plasma clearance (CLplasma) of iohexol by four 1-compartment methods (CL1c), a 2-compartment method (CL2c), and the trapezoidal method (CLtr). Regression analysis was performed to establish correction formulas for prediction of CLtr from the CL1c values and to find optimal times of sampling. Standardization of clearance values to body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…Multiple organ dysfunctions and coagulopathies such as disseminated intravascular coagulation (DIC) are other severe complications that can induce myocard injury [21]. Further, the renal function is often negatively affected in dogs with pyometra which might lead to secondary uraemic myocardial damage [33-35]. In the present study 53% of the pyometra dogs were SIRS-positive, which is in the range of the proportion previously reported [2].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Multiple organ dysfunctions and coagulopathies such as disseminated intravascular coagulation (DIC) are other severe complications that can induce myocard injury [21]. Further, the renal function is often negatively affected in dogs with pyometra which might lead to secondary uraemic myocardial damage [33-35]. In the present study 53% of the pyometra dogs were SIRS-positive, which is in the range of the proportion previously reported [2].…”
Section: Discussionsupporting
confidence: 60%
“…Structural damage of proximal tubuli and some decrease in glomerular filtration rate have been demonstrated in dogs with pyometra [34,35]. Increased cTnI levels have also been demonstrated in azotaemic cats and dogs [37].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between slope‐intercept GFR/ECFV (β) and multisample GFR/ECFV (( A /α +  B /β)/( A /α 2  +  B /β 2 )) in cats was found to be linear in this study and a second order polynomial did not improve the fit of the regression model. This relationship is in agreement with that of 50 dogs undergoing surgery for pyometra28 but contradicts an earlier canine study in which the relationship was found to be nonlinear 15. Slope‐intercept GFR/ECFV has been shown to have a nonlinear relationship with multisample GFR/ECFV in human patients 13, 14.…”
Section: Discussionsupporting
confidence: 73%
“…However, methods for measuring urinary clearance of a substrate require accurate collection of urine, which may be cumbersome in animals. 6 Inulin is one of the markers used for GFR estimation; however, inulin is expensive and sample handling and laboratory analysis of inulin is cumbersome. However, they have greater potential for error if there is extrarenal clearance of the filtration marker or if the pharmacokinetic model used is not appropriate.…”
mentioning
confidence: 99%